Study of microbiological and physicochemical stability of dehydrated foods (Research, Society and Development, 2022)
Dehydration is a process that consists of removing water from a product by evaporation, with heat and mass transfer, reducing contamination by microorganisms. Food dehydration can represent an option in the use of production surpluses and products outside the quality standards for fresh consumption, promoting an increase in shelf life and adding value to the product. The objective of this study was to determine the stability of dehydrated soups, through physicochemical (pH and humidity) and microbiological analyzes (total and thermotolerant coliforms, Staphylococcus aureus, Salmonella, aerobic mesophilic bacteria, fungi and yeasts). These analyzes were performed at intervals of every three months for 60 days. The first analysis performed showed no microbial growth, pH around 5.8 and humidity of 9.0%. In the analyzes carried out after 30 days, growth of mesophilic microorganisms, total and thermotolerant coliforms, Escherichia coli, was observed, while the physical-chemical tests maintained the results close to the previous one, with 9.0% humidity and pH around 5.5. The third analysis, after 60 days, showed growth of total coliforms and yeasts. The physical-chemical tests showed an average humidity of 11.15% and pH around 5.61. Such changes may indicate that the quality of a product varies over time under the influence of several factors, such as storage temperature, humidity and light. Thus, the presence of contaminating microorganisms was observed during the last two analyses.